IFN-γ Producing Th1 Cells Induce Different Transcriptional Profiles in Microglia and Astrocytes - Prajeeth, Chittappen K.; Dittrich-Breiholz, Oliver; Talbot, Steven R.; Robert, Philippe A.; Huehn, Jochen; Stangel, Martin (Frontiers in Cellular Neuroscience, 2018)
Autoreactive T cells that infiltrate into the central nervous system (CNS) are believed to have a significant role in mediating the pathology of neuroinflammatory diseases like multiple sclerosis. Their interaction with microglia and astrocytes in the CNS is crucial for the regulation of neuroinflammatory processes. Our previous work demonstrated that effectors secreted by Th1 and Th17 cells have different capacities to influence the phenotype and function of glial cells. We have shown that Th1-derived effectors altered the phenotype and function of both microglia and astrocytes whereas Th17-derived effectors induced direct effects only on astrocytes but not on microglia. Here we investigated if effector molecules associated with IFN-gamma producing Th1 cells induced different gene expression profiles in microglia and astrocytes. We performed a microarray analysis of RNA isolated from microglia and astrocytes treated with medium and Th-derived culture supernatants and compared the gene expression data. By using the criteria of 2-fold change and a false discovery rate of 0.01 (corrected p-value < 0.01), we demonstrated that a total of 2106 and 1594 genes were differentially regulated in microglia and astrocytes, respectively, in response to Th1-derived factors. We observed that Th1-derived effectors induce distinct transcriptional changes in microglia and astrocytes in addition to commonly regulated transcripts. These distinct transcriptional changes regulate peculiar physiological functions, and this knowledge can help to better understand T cell mediated neuropathologies.